Factors Affecting Consumer Interest in Choosing a Coffee Store in Tangerang District - Bobby Reza; Muhamad Rian Arliony (Enrichment : Journal of Management, 2021)
This study aims to determine the effect of Convenience of Place (X1), Service (X2), Location (X3), Final Quality of Coffee (X4), Taste (X5), Price (X6), Product Diversity (X7) on Consumer Interest (Y ) in Choosing a Coffee Shop in Tangerang Regency. The research method used is a questionnaire distributed via Google Form in several coffee shops in Tangerang Regency. By using quantitative research. The data analysis method used is multiple linear regression analysis by testing the hypothesis, namely the t test and F test with the help of the SPSS 26 for windows program. The sample in this study was 133 respondents who were selected using the Slovin formula. The variables used in this study are Convenience of Place (X1), Service (X2), Location (X3), Final Quality of Coffee (X4), Taste (X5), Price (X6), Product Diversity (X7) as independent variables and Consumer Interest (Y) as the dependent variable. The results of this study indicate that the convenience of place, location and product diversity have a significant effect on consumer interest, but service, final coffee quality, taste and price have no significant effect on consumer interest. Then Convenience of Place, Service, Location, Final Quality of Coffee, Taste, Price and Product Diversity simultaneously have a significant effect on Consumer Interest in Choosing Coffee Shops in Tangerang Regency. And the value of the coefficient of determination (R2) is 0.765 which means that 76.5% of consumer interest is influenced by the convenience of the place, service, location, final quality of coffee, taste, price and product diversity and the remaining 23.5% is explained by other variables outside this research.